2023
DOI: 10.1055/s-0043-1777827
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of Patients with a Mechanical Heart Valve and Poor Anticoagulation Control on Warfarin

Isabelle Johansson,
Alexander P. Benz,
Tanya Kovalova
et al.

Abstract: Background Patients with a mechanical heart valve (MHV) require oral anticoagulation. Poor anticoagulation control is thought to be associated with adverse outcomes, but data are limited. Objective To assess the risks of clinical outcomes in patients with a MHV and poor anticoagulation control on warfarin. Patients/Methods We conducted a retrospective study of consecutive patients undergoing MHV implantation at a tertiary care center (2010–2019). Primary outcome was a composite of ische… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…The study of Johansson et al 5 found an increased risk of adverse events according to the quality of anticoagulation. Patients with a TTR of less than 40% showed a higher incidence of ischemic stroke and embolism, major bleeding, and death.…”
mentioning
confidence: 96%
See 1 more Smart Citation
“…The study of Johansson et al 5 found an increased risk of adverse events according to the quality of anticoagulation. Patients with a TTR of less than 40% showed a higher incidence of ischemic stroke and embolism, major bleeding, and death.…”
mentioning
confidence: 96%
“…Therefore, we read with great interest the recent publication by Johansson et al, 5 who present data from a retrospective observational study evaluating the quality of anticoagulation in patients with MHV and the adverse events that occurred in relation to the quality of anticoagulation achieved. The study reported data from a cohort of MHV patients followed by the anticoagulation clinic (AC) of a Canadian tertiary care level university clinic for a median time of about 5 years.…”
mentioning
confidence: 99%